2008
DOI: 10.1016/j.neuroimage.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site voxel-based morphometry: Methods and a feasibility demonstration with childhood absence epilepsy

Abstract: Aim-Voxel-based morphometry analysis of neurological disorders would benefit if it could use data acquired from different scanners, but scanner based contrast variation could interfere with the detection of disease-specific structural abnormalities. In this study we examine MRI data from three different sites to investigate structural differences between childhood absence epilepsy (CAE) subjects and controls.Methods-T1-weighted structural MRI scans were acquired from: Site A. 10 CAE, 213 controls; Site B. 15 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 18 publications
4
93
1
1
Order By: Relevance
“…Clark et al (2006), investigating scanner/post-processing combinations with optimal segmentation quality, concluded that due to partial voluming effects the thalamic region was susceptible to voxelwise segmentation errors, consistent with our results. Stonnington et al (2008) reached similar conclusions in a study of Alzheimer's disease, but they set out to detect significant scanner effects, as was done by Pardoe et al (2008). In our opinion, the key issues is not merely whether a possible scanner effect is significant or not, as a (just) nonsignificant scanner effect could add a substantial variance, thereby reducing power.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Clark et al (2006), investigating scanner/post-processing combinations with optimal segmentation quality, concluded that due to partial voluming effects the thalamic region was susceptible to voxelwise segmentation errors, consistent with our results. Stonnington et al (2008) reached similar conclusions in a study of Alzheimer's disease, but they set out to detect significant scanner effects, as was done by Pardoe et al (2008). In our opinion, the key issues is not merely whether a possible scanner effect is significant or not, as a (just) nonsignificant scanner effect could add a substantial variance, thereby reducing power.…”
Section: Discussionmentioning
confidence: 66%
“…Ewers et al, (2006) calculated voxelwise coefficients of variance from a single subject scanned on 10 scanners. Pardoe et al, (2008) carried out a multicenter study on childhood absence epilepsy, comparing single-site results and determining between-site differences, while Stonnington et al (2008) analyzed multicenter Alzheimer's disease data to explore whether site-effects were significant. While the last two studies focused on mapping inter-site differences, we set out to map inter-site comparability to show the gain in power, partly comparable with Tardif et al's approach (2009) in sensitivity analysis of 3 T imaging protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, all native GM images were nonlinearly registered to this final template and modulated to account for local expansion (or contraction) because of the nonlinear component of the spatial transformation. The resulting GM density images were smoothed with a Gaussian kernel of 10-mm FWHM, consistent with standard VBM practices (42,43). Finally, we applied log 10 to the smoothed GM density images and regressed out possible effects of age, sex, and intracranial volume (ICV) with a GLM estimated from just 228 CN participants.…”
Section: Methodsmentioning
confidence: 99%
“…The main findings of our study are based on a combined NYU-UCSD dataset. While combining data across different MRI scanners can be problematic, it has become increasingly common in the era of large, multisite neuroimaging studies, 27 and is generally considered appropriate so long as both patients and controls are scanned at each site, and site is included as a covariate in analysis, 28 as we have done. In addition, we analyzed each dataset separately, and results were concordant.…”
Section: 2mentioning
confidence: 99%